Antônio Inácio, mais as suas circunstâncias - Inácio Correia, Antônio; Ribeiro, Eduardo (Argumentos - Revista do Departamento de Ciências Sociais da Unimontes, 2023)
Antônio Inácio, mais as suas circunstâncias